THE INCIDENCE OF LIVER FIBROSIS BASED ON NON-INVASIVE MARKERS AND HEPATOTOXIC DRUG USED IN HEPATITIS B PATIENTS - Achmad, Anisyah; Fadiah, Rara Amalia; Mustofa, Mustofa; Prihadi, Ayu Lestari (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective - The development of hepatitis B virus infection can lead to the asymptomatic liver fibrosis which is reversible, but can develop into cirrhosis or even carcinoma. Hence, laboratory markers are needed to acquire the incidence of fibrosis such as by using AST-to-Platelet Ratio Index (APRI), Fib-4, AST-ALT Ratio (AAR), Age-Platelet (AP) index, and Pohl score. The use of hepatotoxic drug is commonly found in hepatitis B patients that might increase the risk of liver damage. This study aimed to determine the prevalence of liver fibrosis and to discover the use of hepatotoxic drug in hepatitis B patients at Prof. Dr. Margono Soekardjo Purwokerto General Hospital. Methods - This study used total sampling methods with descriptive qualitative and quantitative analysis. The source of data was medical records of hepatitis B patients from January 2012 to August 2013. Results - The result showed that from 25 hepatitis B patients, the incidence of liver fibrosis was found in 8% patients based on APRI, 44% based on Fib-4, 60% based on AAR, 52% based on AP index, and 28% based on Pohl score. There were 12 kinds of hepatotoxic drugs with ranitidine (60%) as the drug most widely used and most of them used one kind of hepatotoxic drug. Conclusions – Our study found that the incidence of liver fibrosis was found in hepatitis B patients which was measured based on APRI, Fib-4, AAR, AP index and Pohl score, beside that the use of hepatotoxic drug was commonly found among those patients.